Factors Influencing Job Performance Among Employees In The Energy And Resource Service Sector In Klang Valley - Noridarizan, Basiran (2024)
Job performance has become a paramount concern for organizations worldwide, given its pivotal role in influencing organizational effectiveness and competitiveness in the era of technological advancement. Recognizing this crucial aspect is essential for organizational success amid the forces of globalization, this study aimed to investigate factors influencing job performance. Specifically, this study examined the influence of training and development, reward and recognition, and proactive personality on job performance. To achieve the research objectives, a survey using questionnaires was conducted among employees in the energy and resource service sector in Klang Valley. A total of 107 responses were gathered and data was analysed using SPSS version 29. The findings reported that training and development has a significant and positive impact on job performance. Nevertheless, other factors have no significant influence on job performance among employees in the sector understudy. In terms of theoretical implications, this study added to the body of knowledge of the respective variables understudy and Social Exchange Theory. As for practical ramifications, the findings from this study serve as a guideline and reference for employers in the energy and resource service sector, especially human resources departments, in developing measures to enhance job performance.